Stress softening effect on changes in the stress-strain state of a tire - Sokolov, Aleksandr Konstantinovich; Svistkov, Aleksandr Lvovich; Komar, Lyudmila Andreevna; Shadrin, Vladimir Vasilievich; Terpugov, Viktor Nikolaevich (Computational Continuum Mechanics, 2016)
The paper reports on a study of the influence of the Mullins softening effect on changes in the stress fields of a rotating car wheel under acceleration and braking conditions. In our opinion, this effect has received little attention in tire industry until recently. Computer modeling of car tire softening is a complex mathematical problem. Therefore, we have developed an algorithm to evaluate changes in the stress-strain of the wheel of the moving car taking into account the Mullins effect. With the algorithm proposed one can study the softening effect in different points of the tire during the first turn of a wheel under acceleration conditions. The results of numerical simulations demonstrate that the softening effect should be taken into account even when developing a simplified model of a car wheel, in which the tire material is considered as isotropic, and the model tire has a simpler geometry than the real tire. It has been found that the deformation of the lateral surface of the tire calculated with the Mullins effect is significantly higher than the deformation obtained in calculations where this effect has been ignored. The hyperelastic fourth-order Ogden model is applied to describe the mechanical properties of an elastomeric matrix of the tire. The degree of softening is evaluated in terms of the Ogden-Roxburgh model. Constants for the model proposed were determined during the cyclic tension test interrupted every 30 minutes after reaching a 5% deformation of the tire.
Keywords: Mullins effect; rubber softening; hyperelastic material; Ogden-Roxburgh model; car tire; finite-element method; computational experiment